A Stability Evaluation of a Nigella sativa Essential Oil Fine Emulsion Containing Sodium Lignosulfonate as the Aqueous Phase - Maria Antonia Tănase; Diana Constantinescu-Aruxandei; Florin Oancea (Proceedings, 2023)
Thymoquinone, the main bioactive ingredient of Nigella sativa essential oil, is known to have important antioxidant, antimicrobial and anti-inflammatory properties [...]